Impacto de las microfinanzas en la vulnerabilidad social del Perú (2012- 2018) - Espinoza Bullón, Gonzalo Sebastián (2023)
This research analyzes the impact of microfinance on reducing social vulnerability in the 24 departments of Peru for the period from 2012 to 2018. The multidimensionality of social vulnerability is ideal to estimate different factors and synthesize them in a single concept expressed numerically in an index. This value will be related to the categories of access and use of microfinance through a panel data model to estimate the impact. The results stipulate that this reduction is partially fulfilled since only loans from microfinance institutions, microfinance offices, and access to the Internet reduce social vulnerability while those that do not are commercial bank loans, telephone lines and gross regional fixed investment. Subsequently, interquartile regression is used to evaluate the effects at three different levels of vulnerability: high, medium and low. From this regression it is concluded that at medium and high vulnerability only microfinance loans reduce vulnerability, while access variables such as internet and number of offices are also significant. In addition, the study reveals that telephone lines increase vulnerability and gross regional fixed investment is not significant. It is recommended to reinforce technological innovation related to connectivity to promote the reduction of vulnerability at the highest levels.